Conservation Biological Control of Pests in the Molecular Era: New Opportunities to Address Old Constraints - Gurr, Geoff M.; You, Minsheng (Frontiers in Plant Science, 2016)
ABSTRACT Biological control has long been considered a potential alternative to pesticidal strategies for pest management but its impact and level of use globally remain modest and inconsistent. A rapidly expanding range of molecular – particularly DNA-related – techniques is currently revolutionizing many life sciences. This review identifies a series of constraints on the development and uptake of conservation biological control and considers the contemporary and likely future influence of molecular methods on these constraints. Molecular approaches are now often used to complement morphological taxonomic methods for the identification and study of biological control agents including microbes. A succession of molecular techniques has been applied to ‘who eats whom’ questions in food-web ecology. Polymerase chain reaction (PCR) approaches have largely superseded immunological approaches such as enzyme-linked immunosorbent assay (ELISA) and now – in turn – are being overtaken by next generation sequencing (NGS)- based approaches that offer unparalleled power at a rapidly diminishing cost. There is scope also to use molecular techniques to manipulate biological control agents, which will be accelerated with the advent of gene editing tools, the CRISPR/Cas9 system in particular. Gene editing tools also offer unparalleled power to both elucidate and manipulate the plant defence mechanisms including those that involve natural enemy attraction to attacked plants. Rapid advances in technology will allow the development of still more novel pest management options for which uptake is likely to be limited chiefly by regulatory hurdles.